2017
DOI: 10.1001/jamaneurol.2016.4357
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features, Molecular Heterogeneity, and Prognostic Implications in YARS2-Related Mitochondrial Myopathy

Abstract: IMPORTANCE YARS2 mutations have been associated with a clinical triad of myopathy, lactic acidosis, and sideroblastic anemia in predominantly Middle Eastern populations. However, the identification of new patients expands the clinical and molecular spectrum of mitochondrial disorders. OBJECTIVES To review the clinical, molecular, and genetic features of YARS2-related mitochondrial disease and to demonstrate a new Scottish founder variant. DESIGN, SETTING, AND PARTICIPANTS An observational case series study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 50 publications
2
51
0
Order By: Relevance
“…60 Furthermore, all patients with biallelic YARS2 mutations do not exhibit CSA, lactic acidosis, and myopathy; patients with only myopathy or CSA plus or minus lactic acidosis are relatively common. [61][62][63] Not only is expressivity of the phenotype highly variable, so is the penetrance of the disease, with genotypically identical siblings having widely divergent hematological phenotypes, including intermittently transfusion-dependent patients with completely phenotypically normal, genetically at-risk siblings. 63 Equally, the anemia in a single patient may wax and wane over time.…”
Section: Isc Biogenesis and Csamentioning
confidence: 99%
“…60 Furthermore, all patients with biallelic YARS2 mutations do not exhibit CSA, lactic acidosis, and myopathy; patients with only myopathy or CSA plus or minus lactic acidosis are relatively common. [61][62][63] Not only is expressivity of the phenotype highly variable, so is the penetrance of the disease, with genotypically identical siblings having widely divergent hematological phenotypes, including intermittently transfusion-dependent patients with completely phenotypically normal, genetically at-risk siblings. 63 Equally, the anemia in a single patient may wax and wane over time.…”
Section: Isc Biogenesis and Csamentioning
confidence: 99%
“…In order to confirm pathogenicity of the identified variants, we expressed both humanized control ( msw1 hI297V , msw1 hE333K ) and mutant WARS2 ( msw1 I297G , msw1 E333M ) in a yeast strain deleted of the WARS2 ortholog gene MSW1 ( ∆msw1 ) (Figure a). Humanized versions were created since the two residues are not conserved, by replacing the yeast aminoacid with the corresponding aminoacid present in the wild type human allele, as previously described (Sommerville et al, ). Humanization of MSW1 did not compromise growth in nonfermentable carbon source and was able to rescue the ∆msw1 strain (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Variants in AARS2 have been associated with leukodystrophy and premature ovarian failure (Dallabona et al, 2014). YARS2 variants cause myopathy, lactic acidosis, and sideroblastic anemia (MLASA2), and severe cases bear some similarity to HLASA while mild cases bear some similarity to the phenotype of Patient 4 (Riley et al, 2018;Riley et al, 2013;Sommerville et al, 2017). In some MLASA2 cases, sideroblastic anemia resolved, as seen in Patients 1 and 2b (Riley et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The central nervous system (CNS) is affected in most mitochondrial aminoacyl-tRNA synthetase-related diseases, with or without involvement of other organs, however, a few of these disorders exclusively affect non-CNS tissues (Gonzalez-Serrano, Chihade, & Sissler, 2019). For some of the mitochondrial aminoacyl-tRNA synthetases, two different phenotypes have been associated with biallelic variants, for example, AARS2 infantile cardiomyopathy (MIM# 614096;Götz et al, 2011), and leukoencephalopathy with premature ovarian failure (MIM# 615889; Dallabona et al, 2014), or a wide range of disease severity has been reported, for example, YARS2 MLASA2 (MIM# 613561) where some cases manifest isolated myopathy or sideroblastic anemia (Riley et al, 2018;Sommerville et al, 2017).…”
Section: Introductionmentioning
confidence: 99%